An analysis of major environmental threats to human security in Nepal - Adhikari, Naresh Bhakta (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
The paper mainly analyses the environmental threats focusing on climate change to human security in Nepal. Major aspects of human security are interlinked and interconnected in our context. Among them, human security offers much to the vibrant field of environmental security in Nepal. Environmental threats are linked to the overall impact on human survival, well-being, and productivity. A great deal of human security is tied to peoples’ access to natural resources and vulnerabilities to environmental change. The major environmental threats in our context is the climate change which have widespread implications for Nepal, causing impacts to water availability, agricultural production, forestry, among many other detrimental effects. The critical threat of environmental security needs to be taken into serious consideration to save our succeeding generation. This article primarily interpreted the government action towards emerging environmental threat based on realist approach. For the study of theme of this article, descriptive and analytical research has been used to draw present major environmental threats in Nepal. With consideration to factors, this article attempted to identify the major environmentally vulnerable areas that are likely to hamper the overall status of human security in Nepal. This paper also tried to suggest the measures to enhance the environmental security considering prospects and policy focusing on Nepalese diverse aspects.